2019
DOI: 10.1371/journal.pone.0221110
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of transcranial direct current stimulation and transcranial magnetic stimulation for chronic orofacial pain: A systematic review

Abstract: Background Transcranial Direct Current Stimulation (tDCS) and Transcranial Magnetic Stimulation (TMS) have been described as promising alternatives to treat different pain syndromes. This study evaluated the effects of TMS and tDCS in the treatment of chronic orofacial pain, through a systematic review. Methods An electronic search was performed in major databases: MEDLINE, Scopus, Web of Science, Cochrane, Embase, LILACS, BBO, Open Gray and CINAHL. The eligibility crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…First, while recent studies focused on the role of VMPFC (Martinez-Perez et al, 2020;Schafer & Frings, 2019;Yin et al, 2021) and DLPFC (Martinez-Perez et al, 2020), the current study provides novel evidence regarding the role of the LpSTS. Second, null results in previous studies might be partially attributed to the relative impreciseness of tDCS targeting while the TMS technique in the current study allows for more precise stimulation (Elder & Taylor, 2014;Ferreira et al, 2019;Kurmakaeva et al, 2021). Third, the usage of HDDM analysis allowed us to separate the effect of TMS on different processing components and indicated that the modulatory effect of LpSTS TMS was manifested in the process of information accumulation (Golubickis et al, 2017(Golubickis et al, , 2020Wiecki et al, 2013).…”
Section: Discussionmentioning
confidence: 68%
“…First, while recent studies focused on the role of VMPFC (Martinez-Perez et al, 2020;Schafer & Frings, 2019;Yin et al, 2021) and DLPFC (Martinez-Perez et al, 2020), the current study provides novel evidence regarding the role of the LpSTS. Second, null results in previous studies might be partially attributed to the relative impreciseness of tDCS targeting while the TMS technique in the current study allows for more precise stimulation (Elder & Taylor, 2014;Ferreira et al, 2019;Kurmakaeva et al, 2021). Third, the usage of HDDM analysis allowed us to separate the effect of TMS on different processing components and indicated that the modulatory effect of LpSTS TMS was manifested in the process of information accumulation (Golubickis et al, 2017(Golubickis et al, , 2020Wiecki et al, 2013).…”
Section: Discussionmentioning
confidence: 68%
“…The following inclusion criteria were applied based on the Participants, Intervention, Comparison, Outcomes, and Study design (Ferreira et al, 2019 ). (1) The participants were healthy adults with no history of musculoskeletal injury and overt neurological disease.…”
Section: Methodsmentioning
confidence: 99%
“…TDCS is applied with weak electric currents at specific times [32][33][34]. A systematic review study in 2019 reported the positive effect of these two methods in reducing chronic orofacial pain [35]. In the systematic review study conducted in 2018 [36], 14 studies (3 TMS studies and 11 TDCS studies) were performed on 228 patients and the results showed that both TMS and TDCS methods are safe and effective treatments for reducing chronic orofacial pain.…”
Section: Low Level Laser Therapy (Lllt)mentioning
confidence: 99%